Linguistic Attitudes of Students: The Power and Social Value of the Lithuanian Language - Poderienė, Nida (Lietuvių kalba, 2025)
The study analyzes the linguistic attitudes of upper secondary school students toward the Lithuanian language based on quantitative data from a survey conducted in Lithuanian schools during the 2023–2024 academic year. The dataset comprises responses provided by students concerning linguistic preferences and attitudes toward Lithuanian. A questionnaire grounded in ethnolinguistic vitality theory was employed to identify the attitudes influencing the linguistic preferences of youth and to analyze trends in the evolution of collective linguistic identity, influenced by the tension between pragmatic value and emotional relation to the language. Attitudes toward the Lithuanian language were examined according to language vitality criteria across several aspects: the pragmatic value and status of Lithuanian, language potential, and its aesthetic and emotional perception. The results indicate that proficiency in Lithuanian has less pragmatic value but relatively high social status in society, as correct Lithuanian is traditionally associated with higher educational attainment. Perceptions of linguistic resources and the level of confidence in Lithuanian are primary drivers of both language change and linguistic preferences. Across the measured aspects, Lithuanian is perceived least positively in terms of modernity and vitality. Most students report that they express themselves best in Lithuanian, however, fewer than half consider the language modern and vibrant. The most positive attitudes are aesthetic, with students regarding Lithuanian as a beautiful language. The findings confirm an association between perceptions of the Lithuanian language and perceptions of the regional dialect. Aesthetic and intuitive perceptions of Lithuanian and of the regional dialect indicate an emotional relation to the language and to the ethnic community.
Keywords: Lithuanian language; youth language; linguistic attitudes; ethnolinguistic vitality; language vitality